Pengaruh Gaya Kepemimpinan Kepala Sekolah, Budaya Organisasi terhadap Kinerja Guru Gugus VI Sekolah Dasar Negeri Lampanah - Husni, Aidi; Akmaluddin, Akmaluddin; Syarfuni, Syarfuni; Sari, Siti Mayang (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The principal is the highest leader in a school institution who has an important role in improving teacher performance in his school. For maximum teacher performance, teachers maintain self-discipline, teachers prepare new learning tools and high teacher creativity in developing learning strategies. This study aims to determine the influence of the principal's democratic leadership style and organizational culture on teacher performance at SDN Cluster VI Lampanah. The approach used is quantitative research with a type of research (causal study) that examines the causal relationship (cause-effect) influence between variables through testing hypotheses that have been formulated. The study population was all principals and teachers of Cluster VI SD Negeri Lampanah using sampling techniques (saturated sampling). The sample of this study amounted to 34 respondents, namely 3 principals and 31 teachers. Hypothesis testing uses a calculation process with a simple regression analysis approach and multiple regression with the help of the SPSS program. The results showed that the principal's democratic leadership style had a significant influence on teacher performance with a contribution of 39.9%, organizational culture had a significant influence on teacher performance with a contribution of 27.1%, and the principal's leadership style and organizational culture together had a significant influence on teacher performance with a contribution of 72.3%.